Juvenile‐onset polyneuropathy in American Staffordshire Terriers. (13th October 2018) - Vandenberghe, Hélène; Escriou, Catherine; Rosati, Marco; Porcarelli, Laura; Recio Caride, Alfredo; Añor, Sonia; Gandini, Gualtiero; Corlazzoli, Daniele; Thibaud, Jean‐Laurent; Matiasek, Kaspar; Blot, Stéphane
Abstract : Background: The only hereditary neurologic disorder described so far in American Staffordshire Terriers is adult‐onset cerebellar degeneration secondary to ceroid lipofuscinosis. We have seen several dogs with a newly recognized neurological disease characterized by locomotor weakness with or without respiratory signs and juvenile onset consistent with degenerative polyneuropathy of genetic origin. Objectives: To characterize a novel polyneuropathy in juvenile American Staffordshire Terriers. Animals: Fourteen American Staffordshire Terriers presented with clinical signs consistent with juvenile‐onset polyneuropathy at 5 veterinary hospitals between May 2005 and July 2017. Methods: Case series. Dogs were included retrospectively after a diagnosis of degenerative polyneuropathy had been confirmed by nerve biopsy. Clinical, pathological, electrophysiological, histological data, and outcome were reviewed and a pedigree analysis performed. Results: All dogs displayed clinical signs of neuromuscular disease with generalized motor and sensory involvement, associated with focal signs of laryngeal paralysis (10/14 dogs) and megaesophagus (1/14 dogs). Histopathological findings were consistent with degenerative polyneuropathy. Follow‐up was available for 11 dogs, and 3 dogs were euthanized shortly after diagnosis. In these 11 dogs, the disease was slowly progressive and the animals maintained good quality of life with ability to walk. Pedigree analysis was mostly consistent with an autosomal recessive mode of inheritance. Conclusions and Clinical Importance: Juvenile polyneuropathy, associated with laryngeal paralysis, is a newly described entity in American Staffordshire Terriers, and results from degenerative neuropathy. When surgery for laryngeal paralysis is performed, lifespan may be similar to that of normal dogs even though affected dogs have locomotor disturbance.